Sistem pengesahan kesahihan dakwaan kena sihir - Nurul Najihah, Che Razali (2014)
Sistem Pengesahan Kesahihan Dakwaan Kena Sihir will help in terms of time savings because only directly key-in data on any computer sessions with victim. Then data directly can be store in database. Besides, it can provide data security features of the data exposed or compromised. Further, it can facilitate Practitioners of Islam Al-Manarah Treatment Center analyzes and identifies validity victims, this system would provide bewitched validity from measurement index. Measurement index provides a range of questions and symptoms that can identify whether the facilitate Islam Al-Manarah Practitioner Treatment Center to identify the victim bewitched or not. Therefore this system can help the judges in divorce causes a fair judge because by measurement index, the victim can be identified. The Al-Manarah Treatment Center will get assist the court in making a decision pending over the years.